Design and analysis of multilayer waveguides containing nanoparticles for solar cells. (1st November 2016) - Shabat, Mohammed M.; El-Amassi, Dena M.; Schaadt, Daniel M.
Highlights: The paper presents a numerical analysis of a new waveguide model for solar cells containing nanoparticles. The obtained results are very useful in design future solar cells models, and the nanoparticles are very promising materials in these design. The model, approach and the types of nano particles could be used in optical sensors technology. The efficiency of solar cells can be tuned and controlled by the types of nanoparticles. Abstract: A novel waveguide structure containing nanoparticles with various substrate media has been proposed to find out the transmission and reflections of the incident light on the proposed structure. The Transfer matrix method has been applied to study the transverse electric TE and the transverse magnetic TM waves at an Antireflection (AR) coating structure for silicon solar cells with a nanoparticles-dielectric layer. The transmission and reflection coefficients have been derived at different incident angles of light and for various substrate's materials in wavelength region between 300 nm and 1200 nm. The numerical results, obtained by MAPLE software, highlight an enhancement of the transmission coefficient and reduction of the reflections for different substrate media.